Survey of filariasis and Microfilarial periodicity in Musi Rawas District, South Sumatra, Indonesia - Edyansyah, Erwin; Mulyaningsih, Budi; Umniyati, Sitti R.; Hadisusanto, Suwarno (International Journal of Research in Medical Sciences, 2021)
Background: Lymphatic filariasis is a parasitic disease that is similar to the threads of its habitat in the lymph system that infect humans, namely Wuchereria bancrofti, Brugia malayi, and Brugia timori. Although B. malayi commonly infects humans, recent evidence also suggests that Brugia pahangi, an afilarial nematode naturally found in cats, can cause clinical infection in humans, with clinical features consistent with lymphatic filariasis. Methods: Cross-sectional with an observational and analytic approach. The results of a positive microscopic examination were carried out by Brugia Rapid Test for B. malayi and PCR examination for B. malayi and B. pahangi. Positive microscopic results were then checked for periodicity of microfilariae every 2 hours for 24 hours Results: From the research, 17 people were positive for B. malayi microfilariae (mf rate 6.34%). The Brugia Rapid Test had 17 positive results. PCR results of 14 people were positive/formed a band at 322 bp. The results of the sample sequencing were B. malayi species. PCR results of B. pahangi were not found to be positive / band formed in all samples. The periodicity results of microfilaria peaked at 00: 00-04: 00 with the nocturnal periodic type. Conclusions: Lubuk Pauh Village, Musi Rawas Regency is still endemic for malayi filariasis with a high level of endemicity and is not an endemic area for filariasis pahangi. The periodicity of microfilariae indicates a nocturnal periodic type.